Different Desensitization Patterns for Sensory and Vascular TRPV1 Populations in the Rat: Expression, Localization and Functional Consequences - Czikora, Ágnes (Public Library of Science, 2013)
BACKGROUND AND PURPOSE: TRPV1 is expressed in sensory neurons and vascular smooth muscle cells, contributing to both pain perception and tissue blood distribution. Local desensitization of TRPV1 in sensory neurons by prolonged, high dose stimulation is re-engaged in clinical practice to achieve analgesia, but the effects of such treatments on the vascular TRPV1 are not known. EXPERIMENTAL APPROACH: Newborn rats were injected with capsaicin for five days. Sensory activation was measured by eye wiping tests and plasma extravasation. Isolated, pressurized skeletal muscle arterioles were used to characterize TRPV1 mediated vascular responses, while expression of TRPV1 was detected by immunohistochemistry. KEY RESULTS: Capsaicin evoked sensory responses, such as eye wiping (3.6±2.5 versus 15.5±1.4 wipes, p<0.01) or plasma extravasation (evans blue accumulation 10±3 versus 33±7 µg/g, p<0.05) were reduced in desensitized rats. In accordance, the number of TRPV1 positive sensory neurons in the dorsal root ganglia was also decreased. However, TRPV1 expression in smooth muscle cells was not affected by the treatment. There were no differences in the diameter (192±27 versus 194±8 µm), endothelium mediated dilations (evoked by acetylcholine), norepinephrine mediated constrictions, myogenic response and in the capsaicin evoked constrictions of arterioles isolated from skeletal muscle. CONCLUSION AND IMPLICATIONS: Systemic capsaicin treatment of juvenile rats evokes anatomical and functional disappearance of the TRPV1-expressing neuronal cells but does not affect the TRPV1-expressing cells of the arterioles, implicating different effects of TRPV1 stimulation on the viability of these cell types.